SELF ASSESSMENT FOR HIGHER LANGUAGE LEARNERS’ AUTONOMY - Gita Mutiara Hati; Wisma Yunita; Anggun Citra Sari Dewi (Universitas Bengkulu, 2021)
The objective of this research is to describe how the use of self-assessment could improve learners’ autonomy. This study employed an action research design involving freshmen of English Education Study Program University of Bengkulu as the subject of the research. This action research was conducted in the Intensive English Course. The cycle of research consisted of plan, action, observation, and reflection. The cycle consisted of fifteen meetings covering four themes of materials. During the meetings, students were instructed to do self-assessment guided by the instructor after they have finished learning each theme. The indicator of success for this research was at least 25% students were categorized as having Very High level of autonomy, while the rest were at High level of autonomy. To measure the level of learners’ autonomy, a questionnaire was used. The questionnaire covers nine aspects of autonomy with the total fifty items. It was given to the subject at the end of the cycle. From the analyzed data, it was found that after only conducting one cycle of the action research, the indicator of success in this research was achieved. Hence, there was no need to continue it to the second cycle. From the result, 30% of students were categorized as having Very High Learning Autonomy.